Synthesis and Electrochemical Characterization of Dissymmetric Tetrathiafulvalene Derivatives for Aqueous Rechargeable Batteries - João F. G. Rodrigues; Isabel C. Santos; Sandra Rabaça; Diogo M. F. Santos (Batteries)
Organic electroactive materials (OEMs) offer advantages such as cost-effectiveness, environmental sustainability, and simplified end-of-life processing compared to inorganic electrode materials. Aqueous electrolytes further enhance sustainability and safety relative to organic electrolytes. Investigating the electrochemical properties of OEMs in aqueous media provides valuable insights into their redox behavior and stability under such conditions. However, challenges remain, including low electronic conductivity and structural stability concerns, while aqueous rechargeable batteries (ARBs) face inherent energy density limitations. Tetrathiafulvalene (TTF) has been previously reported as an electrode material for ARBs, while its oligomers have been proposed for organic electrolyte batteries. This study focuses on the synthesis and characterization of two new dissymmetric TTF derivatives—cyanobenzene tetrathiafulvalene pyrazine (CNB-TTF-Pz) (1) and 4-cyanobenzene tetrathiafulvalene pyrazine (4-CNB-TTF) (2)—as well as one symmetric TTF derivative, dipyrazine tetrathiafulvalene ((Pz)2-TTF) (3). Their electrochemical behavior in aqueous lithium and potassium nitrate electrolytes was systematically characterized using cyclic voltammetry. The study provides insights into the redox properties and electroactivity of these compounds, highlighting challenges related to low electronic conductivity and redox potentials close to the water stability limits. These findings contribute to broadening our understanding of the electrochemical properties of TTF derivatives in aqueous electrolytes and offer a preliminary assessment of their potential application as electrodes for ARBs.